Testing The Day of the Week Anomaly in Different Sectors of the Russian Economy - Nikita PARSHAKOV; Maksim PROKOPOV; Natalia ABRAMOVA (Communications of International Proceedings, 2024)
The article deals with the weekday anomaly in the Russian stock market, with special emphasis on the study of indices of different industries. Using the method of least squares, the authors analyzed the data on industry indices MOEXCH, MOEXEU, MOEXCN, MOEXMM, MOEXFN, MOEXOG, MOEXTL and MOEXTN for the period from January 1, 2012 to August 31, 2024. The results showed that Monday's effect is most pronounced in the oil and gas index, where positive returns are observed with a significance level of 1%. Meanwhile, for other sectoral indices, the effects were not statistically significant. This suggests that anomalies may be temporary and not universal for all sectors. The authors point out the need for continuous monitoring of the anomalies as they tend to change. The results of the paper may be useful for investors seeking to improve their investment strategies based on existing market anomalies.
Keywords: anomaly; day-of-the-week effect; industry indices; stock returns